2017
DOI: 10.18632/oncotarget.21640
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 mediates diabetic renal fibrosis via NF-κB signaling pathway: involvement of CK2α

Abstract: Sphingosine kinase 1 (SphK1) plays a pivotal role in regulating diabetic renal fibrotic factors such as fibronectin (FN) and intercellular adhesion molecule-1 (ICAM-1). Especially, activation of SphK1 is closely linked to the body inflammatory reaction. Casein kinase 2α subunit (CK2α), a protein kinase related to inflammatory reaction, influences diabetic renal fibrosis and expressions of FN and ICAM-1 via NF-κB pathway. However, the mechanism by which SphK1 mediates diabetic renal fibrosis has not yet fully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…Previous studies reported that NF-κB signaling pathway is involved in chronic kidney disease, which mediated inflammation and renal fibrosis 41. Such as protein kinase CK2α and sphingosine kinase 1 ameliorate diabetic renal inflammatory fibrosis through the NF-κB pathway 42,43. In the present study, silibinin decreased the upregulation of phosphorylation of IκB and P65 induced by TGF-β1.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies reported that NF-κB signaling pathway is involved in chronic kidney disease, which mediated inflammation and renal fibrosis 41. Such as protein kinase CK2α and sphingosine kinase 1 ameliorate diabetic renal inflammatory fibrosis through the NF-κB pathway 42,43. In the present study, silibinin decreased the upregulation of phosphorylation of IκB and P65 induced by TGF-β1.…”
Section: Discussionsupporting
confidence: 60%
“… 260 Furthermore, the overexpression of sphingosine kinase 1 was suggested as the mediator of the aberrant CK2 action in the diabetic renal inflammatory fibrosis via NFκB pathway. 261 …”
Section: Ck2 In Human Diseasesmentioning
confidence: 99%
“…In addition, increased expression of S1PR1/2/5 was found in the spleen from mice with anti-GBM Ab GN [ 203 ]. The expression and activity of SphK1 were increased in diabetic kidney [ 198 , 200 , 204 ], MCs [ 198 , 204 ], RTCs [ 94 ] and VSMC [ 205 ], while SphK2 remained unchanged in diabetic kidney, MCs [ 198 ] and VSMC [ 205 ]. SphK1 was overexpressed in podocyte from diabetic patients, while SphK1-deficient mice developed a more severe DN [ 206 ], suggesting a protective role of SphK1 for podocytopathy in DN.…”
Section: Interaction Between Ros and S1p In Oxidant-induced Kidney In...mentioning
confidence: 99%
“…In contrast, deletion of SphK2 decreased neutrophil infiltration in I/R kidney injury [ 259 ], inflammatory macrophage infiltration [ 204 ], TGF-β1 expression, inflammatory cytokines (MCP-1,TNF-α, chemokine ligands-1; CXCL1, and IL-1β) and increased anti-inflammatory (M2) macrophage infiltration in UUO kidney [ 260 ], ameliorating renal inflammation. In addition, SphK2 with Fyn promoted inflammation via STAT3/Akt, while SphK2 knockout reduced it by inhibiting Fyn-STAT3/Akt but not TGF-β1 [ 54 ].…”
Section: Roles Of Mitochondria and Cell Signaling Pathways For S1p-in...mentioning
confidence: 99%